THE EFFECT OF PERCEIVED QUALITY AND PERCEIVED REPUTATION TOWARD ONLINE PURCHASING INTENTION OF ZALORA USER WITH TRUST AS THE MEDIATING VARIABLE - Tjahyadi, Michael Brandon; Tjondro, Michelle Michiko (International Business Management - Universitas Ciputra, 2025)
Due to an increase in individuals remaining at home and purchasing online, the COVID-19 pandemic has also hastened the growth of e-commerce in Indonesia. Furthermore, there have been some reports of unscrupulous merchants and counterfeit goods on e-commerce platforms, so it's crucial for customers to exercise caution and due diligence before making any transactions. The purpose of this research is to analyze the effect of perceived quality and perceived reputation toward purchase intention with the mediating variable of trust. The research conducted in quantitative analysis. The respondent participated in this research are 100 respondents. The data analyzed using Structural Equation Model using SmartPLS3 application. The result explained that perceived service quality, perceived reputation and trust significantly affect purchase intention. Perceived service quality and perceived reputation significantly affect trust. This study is shows that trust, reputation, service quality, and trust have a big effect on purchase intention. The result also found that trust is able to mediate perceived service quality and perceived reputation toward purchase intention. By focusing on these effects, people can make their marketing tactics more effective. Businesses like Zalora can make it easier for customers to buy from them by improving and strengthening these factors.